Faith and state. British policy responses to ’Islamist’ extremism / Fe y Estado. La política británica responde al extremismo ’Islamista’ - Bleich, Erik (Araucaria, 2014)
Islamist extremism has been the focus of intensive global scrutiny since September 2001. Many states have responded to the challenge of Islamic terrorism with a common anti terrorist strategy. Those policies include generic anti violence policies that consciously avoided to mention Islam; repressive policies that explicitly target Muslims extremists and policies that seek to integrate Muslims by soft or compelling methods. The article explores these policies in Britain.